2008
DOI: 10.1111/j.1574-6968.2008.01129.x
|View full text |Cite
|
Sign up to set email alerts
|

Emergence and spread of carbapenem-resistant Acinetobacter baumannii in a tertiary care hospital in Turkey

Abstract: An intensive care unit (ICU)-based OXA-23-producing multiple-drug resistant Acinetobacter baumannii (MDRAB) outbreak was detected between October 2005 and October 2006. A total of 47 patients were infected/colonized with the outbreak strain. Clinical data were available from 37 patients. The all-cause mortality rate among the patients exposed to the epidemic strain was 35% (13/37). The outbreak strain and the resistance determinants were characterized both by microbiological methods and by molecular techniques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Also, plasmids carrying resistance genes and/or resistance determinants involved in horizontal gene transfer have been described in several A. baumannii strains [12][13][14][15][16][17][18][19].…”
Section: Carbapenem Resistance Mechanisms In a Baumanniimentioning
confidence: 99%
See 3 more Smart Citations
“…Also, plasmids carrying resistance genes and/or resistance determinants involved in horizontal gene transfer have been described in several A. baumannii strains [12][13][14][15][16][17][18][19].…”
Section: Carbapenem Resistance Mechanisms In a Baumanniimentioning
confidence: 99%
“…Three main acquired carbapenem-hydrolysing class D oxacillinase (CHDL) gene clusters have been identified either in the chromosome or in plasmids of A. baumannii strains, represented by the bla OXA-23 -, bla OXA-24/40 -, and bla OXA-58 -like genes [12]. Different insertion sequence (IS) elements at the 5' and/or the 3' end of bla OXA-23 -, and bla OXA-58 -like genes, such as ISAba1, ISAba2, ISAba3, or IS18, have been demonstrated to regulate their expression [12,13,[15][16][17]. Also, it has been recently demonstrated that the ISAba1 element is capable of transposition in E. coli and of mobilizing an antibiotic resistance gene [18].…”
Section: Carbapenem Resistance Mechanisms In a Baumanniimentioning
confidence: 99%
See 2 more Smart Citations
“…This bacterium causes a variety of diseases including urinary tract infections, endocarditis, surgical site infections, pneumonia, septicemia, and meningitis (1,5). Numerous strains of A. baumannii have recently emerged to be resistant against a wide spectrum of antibiotics, particularly β-lactams, which have so far been among drug choices for treatment of A. baumannii infections.…”
Section: Introductionmentioning
confidence: 99%